Socially Responsible Investments in the Opinion of Accounting Experts - Remlein, Marzena (Studia Oeconomica Posnaniensia, 2019)
The subject of this study are socially responsible investments understood as investments that combine financial goals with the social, environmental and ethical values of the investor. The aim of the paper is to present the concept of socially responsible investing in the investment activities of business entities and to indicate the shortcomings of financial statements in the presentation of socially responsible investments. The theoretical considerations were supplemented with the results of an empirical study, the purpose of which was to examine the opinion of accounting experts on the essence of socially responsible investments and their presentations in financial statements. The analysis of the literature and the results of the research allowed to formulate postulates regarding socially responsible investments and their presentation in financial statements.